2019
DOI: 10.3892/or.2019.6992
|View full text |Cite
|
Sign up to set email alerts
|

Monocarboxylate transporter�1 is an independent prognostic factor in esophageal squamous cell carcinoma

Abstract: The monocarboxylate transporter 1 (MCT1) has been reported to have significant prognostic value in several solid tumors. The present study aimed to explore its clinical significance in esophageal squamous cell carcinoma (ESCC). After acquiring and analyzing MCT1 (solute carrier family 16 member; SLC16A1) mRNA expression in The Cancer Genome Atlas (TCGA) database, the prognostic potential of MCT1 was assessed by immunohistochemistry (IHC). The impact of the knockdown of MCT1 by shRNA was evaluated using Cell Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…Analysis from previous investigations concerning MCT1 in cancers, regardless of different types [19][20][21][22], revealed that MCT1 prevailed or predominantly over-expressed in cancerous tissues as compared with normal controls and up-regulated MCT1 was found to be linked with poor outcome as well as tumor metastases, which was fully in agreement with our observations in ESCC of our own case. What's congruent with our description with regard to MCT1 is that, in a recent study [18] by Chen X and colleagues, MCT1 was exhibited to be an independent prognostic factor in ESCC. What's different from the study by Chen X et al [18] in that, there was short of functional analysis data of MCT1 in our setting with cell culture system.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Analysis from previous investigations concerning MCT1 in cancers, regardless of different types [19][20][21][22], revealed that MCT1 prevailed or predominantly over-expressed in cancerous tissues as compared with normal controls and up-regulated MCT1 was found to be linked with poor outcome as well as tumor metastases, which was fully in agreement with our observations in ESCC of our own case. What's congruent with our description with regard to MCT1 is that, in a recent study [18] by Chen X and colleagues, MCT1 was exhibited to be an independent prognostic factor in ESCC. What's different from the study by Chen X et al [18] in that, there was short of functional analysis data of MCT1 in our setting with cell culture system.…”
Section: Discussionsupporting
confidence: 91%
“…What's congruent with our description with regard to MCT1 is that, in a recent study [18] by Chen X and colleagues, MCT1 was exhibited to be an independent prognostic factor in ESCC. What's different from the study by Chen X et al [18] in that, there was short of functional analysis data of MCT1 in our setting with cell culture system. Examination of data from these aforementioned literatures along with our own findings about MCT1 in ESCC, explicitly suggested the prognostic value of MCT1 in malignancies, irrespective of their types.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 4 Recent research has identified H3 methylation and monocarboxylate transporter 1 and Jumonji-domain containing 3 expression as biomarkers for the poor prognosis of ESCC. 18 20 Additionally, patients with higher C-reactive protein levels and neutrophil-to-lymphocyte ratios have a better prognosis after chemotherapy. 21 In this study, the clinicopathological characteristics, including sex, age, pathologic stage, G differentiation, and lesion sites, were not significantly correlated with the prognosis of patients with ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis was performed as previously described. 32 The membranes were exposed with an enhanced chemiluminescence reaction (ECL) kit, and the grey levels of the protein bands were analysed using the ImageJ 1.47v software. The sources of the primary antibodies applied were as follows:…”
Section: Western Blot Analysismentioning
confidence: 99%